A multifunctional self-healing G-PyB/KCl hydrogel: smart conductive, rapid room-temperature phase-selective gelation, and ultrasensitive detection of alpha-fetoprotein. Issue 55 (19th June 2019) - Li, Jingjing; Wei, Hongliang; Peng, Yu; Geng, Lifang; Zhu, Limin; Cao, Xiao-Yu; Liu, Chun-Sen; Pang, Huan
Abstract : A self-healing conductive G-PyB/KCl hydrogel exhibited rapid room-temperature phase-selective gelation capacity and ultrasensitive detection of alpha-fetoprotein. Abstract : A multifunctional G-PyB/KCl hydrogel showed outstanding self-healability, high conductivity, and rapid room-temperature phase-selective gelation capacity, and was developed as an electrochemical aptamer sensing platform for the ultrasensitive detection of alpha-fetoprotein.